﻿Catalogue of the Diptera (Insecta) of Morocco- an annotated checklist, with distributions and a bibliography - Kettani, Kawtar; Ebejer, Martin J; Ackland, David M; Bächli, Gerhard; Barraclough, David; Barták, Miroslav; Carles-Tolrá, Miguel; Černý, Milos; Cerretti, Pierfilippo; Chandler, Peter; Dakki, Mohamed; Daugeron, Christophe; et al. (ZooKeys, 2022)
The faunistic knowledge of the Diptera of Morocco recorded from 1787 to 2021 is summarized and updated in this first catalogue of Moroccan Diptera species. A total of 3057 species, classified into 948 genera and 93 families (21 Nematocera and 72 Brachycera), are listed. Taxa (superfamily, family, genus and species) have been updated according to current interpretations, based on reviews in the literature, the expertise of authors and contributors, and recently conducted fieldwork. Data to compile this catalogue were primarily gathered from the literature. In total, 1225 references were consulted and some information was also obtained from online databases. Each family was reviewed and the checklist updated by the respective taxon expert(s), including the number of species that can be expected for that family in Morocco. For each valid species, synonyms known to have been used for published records from Morocco are listed under the currently accepted name. Where available, distribution within Morocco is also included. One new combination is proposed: Assuaniamelanoleuca (Séguy, 1941), comb. nov. (Chloropidae).
Keywords: midges; new records; taxonomy; classification; Bibliography; true flies; new combination; gnats